2014
DOI: 10.1038/ncomms3947
|View full text |Cite
|
Sign up to set email alerts
|

Submicron structures provide preferential spots for carbon and nitrogen sequestration in soils

Abstract: The sequestration of carbon and nitrogen by clay-sized particles in soils is well established, and clay content or mineral surface area has been used to estimate the sequestration potential of soils. Here, via incubation of a sieved (<2 mm) topsoil with labelled litter, we find that only some of the clay-sized surfaces bind organic matter (OM). Surprisingly, <19% of the visible mineral areas show an OM attachment. OM is preferentially associated with organo-mineral clusters with rough surfaces. By combining na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
275
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 327 publications
(298 citation statements)
references
References 44 publications
19
275
4
Order By: Relevance
“…Mineral-N supplementation of N-poor residues can increase C recovery by improving the efficiency of microbial biomass production, decreasing losses of CO 2 -C, and, especially, by increasing deposition of microbial products and debris, which are the main sources of stable SOM associated with mineral particles (Craine et al, 2007;Grandy and Neff , 2008;Manzoni et al, 2008;Vogel et al, 2014). Nevertheless, in this study, the addition of mineral N affected residue-C recovery only in the less stable SOM fraction (LF) (Figure 1a).…”
contrasting
confidence: 39%
“…Mineral-N supplementation of N-poor residues can increase C recovery by improving the efficiency of microbial biomass production, decreasing losses of CO 2 -C, and, especially, by increasing deposition of microbial products and debris, which are the main sources of stable SOM associated with mineral particles (Craine et al, 2007;Grandy and Neff , 2008;Manzoni et al, 2008;Vogel et al, 2014). Nevertheless, in this study, the addition of mineral N affected residue-C recovery only in the less stable SOM fraction (LF) (Figure 1a).…”
contrasting
confidence: 39%
“…The role of clay minerals like illite might be to sequester large amounts of the soil organic matter (Kaiser and Guggenberger, 2003;Vogel et al, 2014) thereby affecting the nutrient availability . The assumption of the reduced availability of nutrients after 3 months is furthermore supported by the significant impact of charcoal, which may adsorb nutrients and reduce their bioavailability (Sohi et al, 2010;Lehmann et al, 2011).…”
Section: Alkane Degraders In Maturating Soilsmentioning
confidence: 99%
“…Several studies therefore concluded that the amount of organic substrates and nutrients present was enough to support activity of the total microflora Babin et al, 2013;Pronk et al, 2013). However, the lower abundance of alkane degraders in soils, maturated for 12 months, in conjunction with the respective stronger response towards litter addition might reflect a depletion of easily bioavailable specific substrates (namely, alkanes) in these soils by degradation and/or maturation-driven reallocation of nutrients to smaller, poorly accessible soil structures (Kö gel- Knabner et al, 2008;Pronk et al, 2012;Vogel et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the remainder of the text, particle borne organic matter will be referred to as particulate matter. This material includes sediment and mineral-bound organic matter trapped in soil micro-aggregates released by soil erosion (Lützow et al, 2006;Mikutta et al, 2006;Remusat et al, 2012), adsorbed or occluded in clay minerals (Vogel et al, 2014) and non-mineral bound organic matter (e.g. litterfalls, roots and other vegetation debris) (Feller and Beare, 1997;Gregorich et al, 2006).…”
Section: Field Samplingmentioning
confidence: 99%